2010 Fifth International Conference on Software Engineering Advances 2010
DOI: 10.1109/icsea.2010.54
|View full text |Cite
|
Sign up to set email alerts
|

Experience Management for Very Small Entities: Improving the Copy-Paste Model

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Although there are pilot projects carried out in multiple countries and other ones are under way (ISO/ IEC 29110 website; http://profs.etsmtl.ca/claporte/english/VSE), only few descriptions of them are available. Outlined below is a brief description of the human factors addressed in (Ribaud, Saliou, & Laporte, 2011;Laporte, Chevalier, & Maurice, 2013;Laporte et al, 2014;Laporte, Herbert, & Mineau, 2014;Laporte & Chevalier, 2015;García Paucar, Laporte, Arteaga, & Bruggmann, 2015;Larrucea et al, 2016).…”
Section: On Human Factors In the Iso 10018 And The Pilot Projects Usi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are pilot projects carried out in multiple countries and other ones are under way (ISO/ IEC 29110 website; http://profs.etsmtl.ca/claporte/english/VSE), only few descriptions of them are available. Outlined below is a brief description of the human factors addressed in (Ribaud, Saliou, & Laporte, 2011;Laporte, Chevalier, & Maurice, 2013;Laporte et al, 2014;Laporte, Herbert, & Mineau, 2014;Laporte & Chevalier, 2015;García Paucar, Laporte, Arteaga, & Bruggmann, 2015;Larrucea et al, 2016).…”
Section: On Human Factors In the Iso 10018 And The Pilot Projects Usi...mentioning
confidence: 99%
“…VSEs can find the efforts or benefit from best practices and performance indicators that the authors of the standard have found so far in the ISO/IEC 29110 (Johansen, Colomo-Palacios, & O'Connor, 2016). Moreover, there is under way an experience factory (Ribaud et al, 2011;Larrucea et al, 2016) that will help VSEs start SPI initiatives.…”
Section: Education and Learningmentioning
confidence: 99%
“…Such need could be one of the reasons behind the fact that few organizations have the resources to adopt the experience factory approach . However, in spite of this barrier, the influence of the approach is obvious in recent works in the software engineering field including aspects like requirements , global software projects and their communication issues , or simple knowledge management systems applied to VSEs . In the VSE's environment, by being part of a community, VSEs could share experiences and practices to take advantage of others' experiences and knowledge and finally improve their software processes .…”
Section: Related Literaturementioning
confidence: 99%
“…An employee of the VSE integrated a training session on requirements based on the training material associated with this Deployment Package. Lessons learned about this training are reported in [8]. Reliability problems reported by the VSE were attributed to the architecture.…”
Section: Back To the Pilot Projectmentioning
confidence: 99%